Original papersIncreased mean platelet volume is associated with coronary artery ectasia - Demir, Serafettin; Avsar, Mustafa Kemal; Karakaya, Zeynep; Selcuk, Murat; Tosu, Aydın Rodi; Abal, Gulcan; Tokuccu, Eda; Demir, Mesut (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Aim: The present study was designed to investigate mean platelet volume (MPV) values in coronary artery ectasia (CAE) patients in comparison with individuals with coronary artery disease and normal coronary angiograms. Material and methods: Patients with stable angina pectoris and scheduled for angiography were included in the study. Those with isolated coronary ectasia were evaluated in the coronary angiography. Mean platelet volume was measured in 126 patients (mean age: 57.2 ±11.3 years) with isolated CAE, 126 patients (mean age: 56.3 ±10.4 years) with coronary artery disease (CAD) and 122 control subjects (mean age: 58.1 ±11.1 years). Coronary artery ectasia was defined as lack of stenotic lesion, on visual assessment, of the coronary arteries with a luminal dilatation 1.5-fold or more of the adjacent normal coronary segments. Mean platelet volume values were recorded in all patients. Ectasia severity was evaluated and categorized in accordance with the Markis categorization. Results: A significant difference with respect to age, sex, hypertension, diabetes mellitus, and cigarette use between the study groups was not found (p > 0.05). Mean platelet volume was significantly higher in patients with CAE and CAD than in the control group (9.8 ±3.8 fl and 9.7 ±3.9 fl vs. 8.8 ±3.3 fl, p < 0.001). There were no statistically significant differences between CAE and CAD groups. When type I and type IV subgroups were compared in patients with coronary artery ectasia, MPV was detected as statistically high in the type I subgroup (p = 0.026). Conclusions : It was shown that patients with CAE and CAD have higher MPVs than subjects with normal coronary angiograms. Moreover, it was detected that in coronary artery ectasias, the increase in MPV is related to both the atherosclerotic process and severity of the disease.